Secure Digital Certificate Design Based on the Public Key Cryptography Algorithm - Zhang Qi ming (Institute of Advanced Engineering and Science, 2013)
With the popularity of the Internet, more and more people choose online shopping, however, in the case of lacking security measures, there is a great deal of risk on the Internet. to this situation,In response to this situation, this paper presents a digital certificate based on the X.509 standard. This paper uses the C language generation public key algorithm (RSA). Realization of the digital certificate registration, verification and certificate generation process,the identity of certification users can be verified and provide proof of identity on the Internet transactions, reducing the transaction risks greatly, ensuring the user's property and interests are not infringed. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3824